KEBIJAKAN PENGEMBANGAN KOLEKSI: AKUISISI KOLEKSI DI PERPUSTAKAAN PERGURUAN TINGGI TRINITY DUBLIN - Hayatuddiniyah Hayatuddiniyah (Fihris: Jurnal Ilmu Perpustakaan dan Informasi, 2021)
This article aims to investigate the collection activities carried out by the Dublin Trinity College Library as part of the collections development process. The method used in this article is a qualitative method, and the data collection technique uses literature studies. Dublin Trinity College Library is one of the higher education libraries in Ireland which has a collection of more than 6 million printed volumes with a collection of journals, manuscripts, maps and music. The collection's acquisition as a collection development undertaken by the Dublin Trinity College Library was a purchase and a grant. Purchases are made independently with predetermined criteria such as collections that support teaching, learning, and research at Trinity Dublin College. And acquisitions through grants consist of providing copies of archives and documents published by the Commonwealth of England, namely the British and Irish intelligence.